Unconventional Source and Shale Oil Potential of Upper Cretaceous Rakb Group in The NC84 East Sirte Basin, Libya - Hallash , Abdalmonem H. (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
This study focused on geochemical analysis of the Rakb group from two wells A2 and B2 in the NC84 east Sirte basin, where deal with this rocks as unconventional source, the samples were analysis by used Rock Eval pyrolysis. The results of this research showed total organic matter range from 0.4% to 2.6% categorized as fair to good source, and organic matter are Type II and type III kerogen. The maturity of the Rakb group are in mature zone (oil window). Oil saturation OSI of the samples range from 20 to 482 mg HC/g TOC that lead to the Rakb rocks have capacity to produce shale oil.